Improving Shadow Teachers Competence through the REACH Website in an Inclusive Curriculum Based on Religiosity and Self-Awareness - Anita Puji Astutik; Nadhirah Nordin; Isna Meilinda (ISTIFHAM, 2026)
This study aims to develop the REACH website “Religious Empowerment and Competent Assistance” in improving the competence of shadow teachers in implementing the inclusive curriculum at Muhammadiyah 2 Elementary School, Tulangan. The research method used is Research and Development (R&D) with the ADDIE model which includes: analysis, design, development, implementation, and evaluation, with 27 shadow teachers as research subjects. The results of the study are shown in the Paired Samples Test table, where a significance value (Sig. 2-tailed) of < 0.001 was obtained, which is smaller than the significance level of 0.05. This indicates that there is a significant difference between the pretest and posttest scores. With these significant improvement results, it can be said that the REACH website  is effective in improving religious competence and self-awareness in the inclusive curriculum at Muhammadiyah 2 Elementary School Tulangan.